Mapping coral cover using Sentinel-2A in Karimunjawa, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Satya ED, Sabdono A, Wijayanti DP, Helmi M, Widiaratih R. 2023. Mapping coral cover using Sentinel-2A in Karimunjawa, Indonesia. Biodiversitas 24: 827-836. Coral reefs in the Karimunjawa National Park (KNP) have their own charm, especially for snorkeling and divers, it can be seen from the number of tourist visits which tends to increase every year, except for 2020 to 2021 due to the COVID-19 pandemic. This study aims to determine the impact of tourism on coral reef cover in KNP, with islands selected as representatives of high, medium and low level of tourist visits using Sentinel-2A. Comparison of Sentinel-2A coral cover area in 2020 with previous research which used Landsat 8 data in 2018 showed decrease in coral cover area by 16.5% and an increase in sand area by 24.1% for island of high tourist visits. It can be seen that tourism activities have significant impact on coral cover area, especially snorkeling and diving activities that are intentional or not potentially damaging to coral reefs. Sentinel-2A's ability to detect coral area is reliable, since field data is needed as input for data processing to identification locations in detail as needed. Coral area in 2020 using Sentinel-2A obtained for Menjangan Besar Island and Menjangan Kecil, Sintok Island, Tengah Island and Seruni Island were 1.88 km2, 0.303 km2, 0.318 km2, 0.237 km2 respectively.
Keywords: Coral cover, KNP, level tourist visiting, sand cover, Sentinel-2A